Summary of the 2016 Alcohol and Immunology Research Interest Group (AIRIG) meeting. - Boule, Lisbeth A.; Ju, Cynthia; Agudelo, Marisela; Parira, Tiyash; Cannon, Abigail; Davis, Booker; Eby, Jonathan; Cresci, Gail; Samuelson, Derrick R.; Shukla, Pradeep; Alrefai, Waddah A.; Sureshchandra, Suhas; et al. (Alcohol, 2018)
On November 18, 2016 the 21st annual Alcohol and Immunology Research Interest Group (AIRIG) meeting was held at the Center for Translational Research and Education at Loyola University Chicago's Health Sciences Campus in Maywood, IL. The 2016 meeting focused broadly on alcohol and inflammation, epigenetics, and the microbiome. The four plenary sessions of the meeting were Alcohol, Inflammation, and Immunity; Alcohol and Epigenetics; Alcohol, Transcriptional Regulation, and Epigenetics; and Alcohol, Intestinal Mucosa, and the Gut Microbiome. Presentations in all sessions of the meeting explored putative underlying causes for chronic diseases and mortality associated with alcohol consumption, shedding light on future work and potential therapeutic targets to alleviate the negative effects of alcohol misuse.